'Is America afraid of the truth?' The aborted North American trip of Shapuriji Saklatvala, MP. (July 2016) - Zumoff, J.A.
In the fall of 1925, S.J. Saklatvala, an Indian-born Communist Member of the British Parliament, attempted to travel to the United States for the annual meeting of the Interparliamentary Union. At the last minute, the US government revoked his visa because of his Communist politics. This article examines this affair, analyses American government's decision and the British government's reaction, and places this in the context of the anti-Communist sentiment in Britain and the United States during the 1920s. Finally, the article examines the unsucessful campaign against the ban, emphasising how the campaign allowed Communists to build support among different sectors of the population.